Measurement of the branching ratio Γ(<msubsup is="true">Λb0</msubsup>→ψ(2S)Λ0)/Γ(<msubsup is="true">Λb0</msubsup>→J/ψΛ0) with the ATLAS detector - Alconada Verzini, María Josefina (2015)
An observation of the <msubsup is="true">Λb0</msubsup>→ψ(2S)Λ0 decay and a comparison of its branching fraction with that of the <msubsup is="true">Λb0</msubsup>→J/ψΛ0 decay has been made with the ATLAS detector in proton–proton collisions at <msqrt is="true">s</msqrt>=8<mtext is="true"> TeV</mtext> at the LHC using an integrated luminosity of 20.6 fb−1. The J/ψ and ψ(2S) mesons are reconstructed in their decays to a muon pair, while the Λ0→pπ− decay is exploited for the Λ0 baryon reconstruction. The <msubsup is="true">Λb0</msubsup> baryons are reconstructed with transverse momentum pT>10<mtext is="true"> GeV</mtext> and pseudorapidity |η|<2.1. The measured branching ratio of the <msubsup is="true">Λb0</msubsup>→ψ(2S)Λ0 and <msubsup is="true">Λb0</msubsup>→J/ψΛ0 decays is Γ(<msubsup is="true">Λb0</msubsup>→ψ(2S)Λ0)/Γ(<msubsup is="true">Λb0</msubsup>→J/ψΛ0)=0.501±0.033(stat)±0.019(syst), lower than the expectation from the covariant quark model.